2010
DOI: 10.1080/01639360903586464
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Supplements for Older Adults: Review and Recommendations—Part II

Abstract: The use of nutritional supplements (NS) with the intention of improving health and delaying age-related chronic disease is a common practice among older adults; however, randomized controlled trials have yielded mixed results regarding the likelihood that these NS provide true health benefits. We reviewed the findings of these studies regarding the effects of NS of folic acid, vitamin B(12), vitamin B(6), and omega-3 fatty acids on health outcomes in older adults. Our conclusions include the following: Supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 100 publications
0
14
0
1
Order By: Relevance
“…B12 deficiency has been linked to neuropsychiatric symptomatology and suggestions have been made for oral B12 supplementation of the older age people suffering late-life depression (Coppen & Bolander-Gouaille, 2005;Hin et al, 2006), although evidence is so far inconclusive (Buhr & Bales, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…B12 deficiency has been linked to neuropsychiatric symptomatology and suggestions have been made for oral B12 supplementation of the older age people suffering late-life depression (Coppen & Bolander-Gouaille, 2005;Hin et al, 2006), although evidence is so far inconclusive (Buhr & Bales, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although omega-3 fatty acid supplementation has been shown to reduce CV events in some studies, a recent randomized trial in patients 60–80 years old with prior MI showed no significant effects on new major CV events (132). There is little evidence to suggest a benefit from B vitamin supplementation in preventing CV disease in seniors (133). …”
Section: Lifestyle Therapy Of Ascvdmentioning
confidence: 99%
“…Compared with vitamin D, the benefits of added calcium for depression are less certain. Intake of 1200 mg calcium daily is recommended to combat osteoarthritis and associated disability 81, 82. Depression may be associated with low bone mass, which can benefit from the supplementation of calcium 83.…”
Section: Treatmentmentioning
confidence: 99%